Ideal minds : raising consciousness in the antisocial seventies - Trask, Michael, 1967- (Cornell University Press, 2020)
"Ideal Minds is equal parts intellectual and literary history of the recent past. Combining ideas from a mix of disciplines, the book also delves into more esoteric branches of learning, like Scientology, anarchist theory, rapture prophesies, psychic channeling, and neo-Malthusianism. The book's central premise is that a dramatic inflation in the value of consciousness and autonomy beginning in the 1970s accompanied a recognition of the state's refusal to safeguard such values."--